Transportation Among Returning Citizens: “You Just Want to Stay Down and Get High” - Davis, Jaya B. (International journal of offender therapy and comparative criminology, 2023)
The United States is releasing more individuals from prisons than ever before. However, returning citizens face numerous challenges transitioning back into community life and many communities remain ill-equipped in successfully supporting them. This study focuses on transportation as in integral component to the success of returning citizens. Rapid and rigorous qualitative data analysis (RADaR technique) is applied to interviews (n = 15) with individuals having returned to their community about the impact of transportation on their reentry. Analysis resulted in three primary themes; interviewees reinforced existing knowledge of the issues with transportation disadvantage, transportation is an extension of freedom, and transportation is directly connected to reentry success. These findings suggest a tiered structure of transportation freedom for returning citizens. This model of transportation will aid future researchers and policymakers in considering how to better resource returning citizens to maximize their success.